What Is the Impact of Business Investment on Euronext Stock Returns? - Luís COSTA; Elisabete VIEIRA; Mara MADALENO (Communications of International Proceedings, 2024)
This work aims to analyze the impact that companies' investment has on some Euronext stock returns. To this end, a sample of companies was collected from the Amsterdam, Brussels, Paris, and Lisbon stock exchanges between the years 2017 and 2022, using the Generalized Method of Moments (GMM). The results demonstrate that the investment has a positive and significant impact on Euronext stock returns. This conclusion suggests that managers of Euronext companies should seek to have a balanced investment strategy that incorporates tangible and intangible assets to maximize stock returns. This study can help in decision-making for private and institutional investors who invest in Euronext stocks. The originality of this article lies in the analysis of the impact that investment, broken down into tangible and intangible assets, has on the returns on Euronext stocks. Finally, it is important to mention that the use of the GMM methodology allowed robust results to be obtained.
Keywords: Stock Returns; Euronext; Investment; Cash Flow